The Potential of Biochar for Heavy Metal Adsorption in Acid Mine Drainage Based on Literature Review - Simamora, Eprilia; Nurcholis, Mohammad; Ardian, Aldin; Ernawati, Rika; Winarno, Eddy (Journal of Earth and Marine Technology (JEMT), 2024)
Incorporating organic materials that contain biochar is gaining traction as a research area for the cleanup of wastewater contaminated with heavy metals. This study intends to explore the potential of biochar-based materials in removing heavy metals from water sources, with a particular emphasis on rehabilitating aquatic environments affected by mining waste. Identifying appropriate literature studies in collecting research data from various scientific publications was used to understand the topic. Several biochar manufacturing processes are generated through pyrolysis, gasification, and Hydrothermal carbonization (HTC). In this field, studies revealed that using most biochar can achieve relatively high metal removal. Research findings indicate that Cu, Zn, Cd, Pb, Ni, Cr, Co, As, Ag, Fe, Al, and Mn are the metal ions that have received the most attention in this field. This study highlights explicitly the effectiveness of biochars made from orange peel, nutshell, compost, rice husk, oak wood, used coffee grounds, durian bark, Phragmites australis corn cob, dregs of cascara, and hickory wood. The findings show that biochars from these materials, especially those produced at high pyrolysis temperatures (≥500°C), can achieve metal removal efficiencies above (≥90%). Various factors can influence the effectiveness of biochar in removing heavy metal ions, including the pH of the contaminated water, the amount of biochar used, the initial concentration of heavy metals, the properties of the biochar, and the specific forms or speciation of the metals. Biochar's ability to draw in and retain metal ions can be influenced by its characteristics, including its surface area and pore sizes. This study highlights the need for more research in this field going forward. It gives a general review of the use of biochar in removing heavy metals from water, particularly contamination in Acid Mine Drainage (AMD).